Volume 6: Ceramics; Controls, Diagnostics, and Instrumentation; Education; Manufacturing Materials and Metallurgy 2019
DOI: 10.1115/gt2019-92087
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Temperature Measurement With Thermal History Paints: An Uncertainty Estimation Model

Abstract: The operating temperature of turbomachinery components are increasing the drive towards higher efficiency, lower fuel consumption and reduced emissions. Accurate thermal models are required to simulate the operating temperature of gas turbine components and hence predict service life or other qualities. These models require validation through measurement. Therefore, the quality of the models and prediction are dependent on the uncertainty of the measurements used to validate them. Currently avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These can be divided into contributions from the calibration procedure and the decay time measurement in the experiment itself. Similar to Peral et al we identified the thermocouple measurement during the calibration and the decay time measurement as the main contribution to measurement uncertainty [19]. Systematic errors from differences in the experimental setup between experiment and calibration were greatly reduced by using the same optics where possible and the same electronics.…”
Section: Phosphor Selection and Calibrationsupporting
confidence: 61%
“…These can be divided into contributions from the calibration procedure and the decay time measurement in the experiment itself. Similar to Peral et al we identified the thermocouple measurement during the calibration and the decay time measurement as the main contribution to measurement uncertainty [19]. Systematic errors from differences in the experimental setup between experiment and calibration were greatly reduced by using the same optics where possible and the same electronics.…”
Section: Phosphor Selection and Calibrationsupporting
confidence: 61%
“…This makes FEM2D models more suitable for comparison with experimental data. In order to validate complex thermal models over 80% of the surface should be measured, which is not possible with point measurement systems such as thermocouples [18]. Thermal maps allow manufacturers to better understand the effects of air flow on specific areas of components, which can help to improve the life cycle of a part.…”
Section: Numerical Methods For Temperature Estimationmentioning
confidence: 99%
“…Exposure to high temperatures increases the risk of failure, which makes health monitoring of these components vitally important. During the design stage, finite element models are often used to predict thermal stresses but are difficult to verify experimentally [11]. Additional high temperature sensors can feed into active control systems to ensure optimal operation of complex systems.…”
Section: Introductionmentioning
confidence: 99%